Use Of Big Book Media Towards Interest In Reading Elementary School Students (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
This research is motivated by the low interest of students, especially in reading interests. The learning media uses big book media. This study aims to determine the use of big book media on the reading interest of elementary school students in grade II in Pulokalapa II Elementary School because when observing in Pulocalapa II Elementary School, not all students have a high interest in reading and a lack of interesting learning media. This research is descriptive qualitative research. The research subjects were all grade II students of Pulocalapa II Elementary School, totaling 27 students consisting of 15 female students and 12 male students. Data collection methods used were observation, questionnaire/questionnaire, interview, and documentation. Research shows that the use of big book media is said to be successfully applied in the lower classes to foster interest in reading. From the results of the research that has been done, it can be concluded that the use of big book media can foster interest in reading elementary school students in grade II of SDN Pulokalapa II in the 2018/2019 school year.